Pengaruh Stres Kerja dan Kepuasan Kerja Terhadap Kinerja Pegawai Dinas Kependudukan dan Pencatatan Sipil Kota Padang - Julio Darma Putra; Dewirahmadanirwati Dewirahmadanirwati (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This research was conducted to determine the effect of job stress and job satisfaction on employee perfomance on population and civil registration office Padang city. This research method uses quantitative methods. The technique used in collecting data in this research is a questionnaire by distributing questionnaires to 72 respondents using population and civil registration office Padang city, and the data from the respondents' answers will be processed using SPSS. The results of this study indicate that job stress has a positive effect on employee perfomance, job satisfaction does notaffect on employee perfomance.